PEDAGOGICAL ANALYSIS OF IMPROVING THE HEALTHY LIFESTYLE AND PHYSICAL CULTURE OF STUDENTS IN GENERAL EDUCATION SCHOOLS - Saidmaxmud, Mirzayev (Research Focus International Scientific Journal, 2026)
The article presents a pedagogical analysis of improving the healthy lifestyle and physical culture of students in general education schools. It widely covers young people’s attitude toward the formation of a healthy lifestyle, ways of organizing pedagogical technology- based classes, and their methods.